Management of split skin graft donor site in the west african sub region: survey of plastic surgeons’ practice. (2017)
Split skin graft (SSG) is one of the most commonly performed operations on any Plastic Surgery service. Rate of donor site healing is affected by various factors including the type of dressing applied. The aim of this study was to survey the practice of plastic surgeons in the sub region with respect to management of SSG donor site and see how it conforms to international standards. Structured questionnaires on various aspects of the harvest and management of SSG donor sites were administered to plastic surgeons during the 53rd annual conference of the West African College of Surgeons (WACS) at Lome, Togo in March 2013. The data were analyzed using descriptive statistics. There were 47 respondents out of 55 plastic surgeons from four West African countries, which represented 85.4% of registered participants at the plastic surgery section of the conference. All the respondents performed SSG regularly, and the thigh was the most commonly used donor site. Different types of paraffin gauze remained the most commonly used primary donor site dressing. Only 17% of the respondents apply a topical local anaesthetic agent on the donor site. The choice of SSG donor site dressing in the sub region was driven mainly by availability. Concerted efforts must be made to access newer wound care products for optimum management of this commonly performed operation.